Kolaviron and vitamin E ameliorate hematotoxicity and oxidative stress in brains of prepubertal rats treated with an anticonvulsant phenytoin (2014)
Phenytoin (PHT), an anticonvulsant agent, widely used for the treatment of epilepsy has been reported to exhibit toxic side effects. The present study investigated the protective effects of kolaviron and vitamin E on hematotoxicity and neurotoxicity induced by phenytoin, in prepubertal male rats. The animals were treated with PHT (75 mg/kg) separately or in combination with either kolaviron (200 mg/kg) or vitamin E (500 mg/kg) for 14 days. Phenytoin treatment significantly decreased the hemoglobin, white blood cells, lymphocytes and mean corpuscular volume levels without affecting red blood cell, packed cell volume, neutrophils, mean corpuscular hemoglobin and mean corpuscular hemoglobin concentration when compared with the control rats. There was a significant increase in lipid peroxidation and hydrogen peroxide levels with marked depletion in antioxidant status in brains of PHT-treated rats when compared with the control. Although PHT treatment had no effect on the granular layer, widest diameter of Purkinje cells and Purkinje layer of the cerebellum, it significantly reduced its molecular layer and the density of Purkinje cell. Administration of PHT significantly reduced the densities of the granule cells of the dentate gyrus and the pyramidal neurons of the cornu ammonis of hippocampus proper. Co-treatment with kolaviron and vitamin E effectively reversed the PHT-mediated alterations in the hematology, brain antioxidant status and histomorphometry when compared to PHT only. Taken together, the present data indicate the abilities of kolaviron and vitamin E to ameliorate phenytoin-induced hematotoxicity and oxidative stress in brains of rats.